Personal Selling Moderating Values and Price on Revisit by Mediating Customers’ Satisfaction - Bintarti, Surya; Nur'aeni, Nur'aeni; Permana, Indra; Nurpatria, Ergo (Interdisciplinary Social Studies, 2023)
Background: Millennials tend to want to try everything they see on the internet, characters who like to try and be expressive as an example of one of them are food, this of course affects the lifestyle of the millennial generation. Various kinds of bakeries spread across Indonesia, sales of Holland Bakery always occupy the third position. Holland Bakery offers a variety of interesting products to consumers. Aim: This study aims to examine the relationship between perceived value and price on repurchase intentions through the mediation of consumer satisfaction moderated by personal selling. Methods: This research uses quantitative methods. Sampling in this study used the Non Probability Sampling Method with a purposive technique. The population used by the community in Bekasi district. The samples obtained were 100 consumer respondents who consumed Holland Bakery. This research data analysis fully uses SmartPLS 4.0. Findings: Personal selling can play a role in strengthening the perceived value of consumer repurchase intentions of Sari Roti and BreadTalk brand bread , but not so for Holland Bakery brand products that personal selling has a direct role on repurchase intention. Personal selling can play a role in strengthening the price of consumer repurchase intentions of Holland Bakery and BreadTalk brand bread, but not so for Sari Roti brand products that personal selling has a direct role on repurchase intention.